Histopatologi Organ Pankreas Tikus DM tipe 2 yang diberi Ekstrak Etanol Daun Gedi Merah (Abelmoscus manihot L. Medik) - Nuralifah Nuralifah; La Ode Muhammad Fitrawan; Parawansah Parawansah; Mesrawati Trisetya (Journal Syifa Sciences and Clinical Research, 2022)
Gedi Merah leaf (Abelmoschus manihot L.Medik) is a tropical plant used by the community as a traditional medicine to reduce cholesterol, hypertension, and antidiabetic levels. Diabetes mellitus is a disorder of carbohydrate, protein, and fat metabolism due to a lack of the hormone insulin so that glucose in the blood increases which is characterized by changes in the histopathological structure of the pancreatic islets of Langerhans. The purpose of this study was to see the histopathological description of the pancreas in male white rats (Rattus norvegicus) Wistar strain model of type II diabetes mellitus by administering ethanol extract of red gedi leaves (Abelmoschus manihot L.Medik). Modeling of diabetes mellitus in experimental animals was carried out by administering a high-fat diet and intraperitoneal induction of streptozotocin 30 mg/kg. After modeling, male rats were grouped into 6 treatment groups, namely a normal control group, a positive control group, a negative control group, and a group that was given the ethanol extract of red gedi leaves at a dose of 75 mg/kg BW, 150 mg/kg BW 300 mg/kg BW. The results of the histopathological examination of the pancreas and the number of endocrine cells showed that the ethanolic extract of red gedi leaves (Abelmoschus manihot L.Medik) was effective in repairing pancreatic cells and regenerating endocrine cells in the islets of langerhans.